COMPLEMENTS REGARDING THE DYNAMIC STABILITY OF THE SYNCHRONOUS MACHINE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper analyzes factors conditioning the dynamic stability of a high power synchronous motor, by using non-linear dynamic mathematical models. There is noticed a structural difference between the dynamic angular characteristics compared to the static angular characteristics. There result notable electrical, magnetic and mechanical stresses, which must be necessarily considered, in the stage of design and exploitation.